Transformation ratio at wakefield excitation by linearly shaped sequence of short relativistic electron bunches in plasma - Levchuk, I.P.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2015)
Wakefield excitation by long sequence of short Gaussian bunches of relativistic electrons and electron bunch acceleration in excited wakefield is numerically simulated for the parameters of the experiments. It is shown that at change of the system parameters and shaping laws of sequence of bunches of relativistic electrons in the intervals of finite width the transformation ratio remains large. Числовим моделюванням досліджується для параметрів експериментів збудження кільватерного поля до-вгою послідовністю коротких гауссівських згустків релятивістських електронів і прискорення електронних згустків з малим зарядом у збудженому полі. Показано, що при зміні параметрів системи і законів профілювання послідовності згустків релятивістських електронів в інтервалах кінцевої ширини коефіцієнт трансформації залишається значним. Численным моделированием исследуется для параметров экспериментов возбуждение кильватерного по-ля длинной последовательностью коротких гауссовских сгустков релятивистских электронов и ускорение электронных сгустков с малым зарядом в возбужденном поле. Показано, что при изменении параметров системы и законов профилирования последовательности сгустков релятивистских электронов в интервалах конечной ширины коэффициент трансформации остается большим.